Poskusni program rehabilitacije s pomočjo psov - Kovačič, Dare (Rehabilitacija (Ljubljana), 2008)
Background: We conducted an experimental animal (dog) assisted activity and therapy (DAAT) program and a paralel study on patients' response. Methods: The treatment took place in groups of six to eight patients, three dogs and three therapists. All together 60 patients, 33 males and 27 females, 35 with traumatic brain injury, 13 with multiple sclerosis and 12 with other diagnoses participated in 130 hours of DAAT. Their response (alertness, attention, movement, activity, emotional and motivational state) was assessed on a five-point scale from -2 to +2. Results: The great majority, 93%, of patients responded positively, during the DAAT they were active, attentive and in the good mood. The average estimates of response of gender and disability diagnosis subgroups were between 1,38 and 1,52, i.e. between positive and very positive, with no significant differences among patient groups. The relatives of six TBI patients estimated that during DAAT patients were significantly more active, more alert and attentive, and showed better mood than otherwise in last week; they also estimated that the effect on patients' health state and satisfaction was significantly positive. Conclusions: DAAT is primarily effective for the disabled in elementary functions (movement, activity, alertness, attention, cognition, motivation); for persons who are lonely, persons with depressive disorders, anxiety disorders, communication disabilities; for children, adolescents and aged ones. Professional and scientific literature findings, everyday experiences and results of this study support the inclusion of DAAT as additional treatment in the process of integral rehabilitation.
Keywords: neurology; nevrologija; multipla skleroza; možganske poškodbe; rehabilitacija; vocational rehabilitation; dogs; psi